1986
DOI: 10.1002/bjs.1800730713
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aneurysms in a black population: Clinicopathological study

Abstract: With exclusion of vascular trauma 2182 patients (1302 black and 880 white) have been treated in our Vascular Service over a period of 3 years. Sixty black patients (4.6 per cent) and 260 white patients (29.5 per cent) presented with aneurysms of the aorta and its abdominal branches. The aneurysms in the black group were distributed as follows: 50 aortic (9 suprarenal, 41 infrarenal), 6 common iliac artery, 2 superior mesenteric and 2 renal artery aneurysms. None of the 260 aneurysms seen in white patients invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
3

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 11 publications
0
18
3
Order By: Relevance
“…176 Data from South Africa also suggest that the typical 'atherosclerotic' infra-renal AAA seen in whites is uncommon in the black population. 193 With regard to Asians, a study form Bradford, UK, where south Asians comprise 14% of the population, found that none of 233 patients undergoing AAA repair between 1990 and 1997 were south Asian. 194 As with lower limb PAD and rates of lower limb revascularization, it is difficult to know to what extent these data reflect lifestyle, socio-economic factors, unmet health care need or true ethnic and racial differences in the disease processes or access to services.…”
Section: Secondary Preventionmentioning
confidence: 98%
“…176 Data from South Africa also suggest that the typical 'atherosclerotic' infra-renal AAA seen in whites is uncommon in the black population. 193 With regard to Asians, a study form Bradford, UK, where south Asians comprise 14% of the population, found that none of 233 patients undergoing AAA repair between 1990 and 1997 were south Asian. 194 As with lower limb PAD and rates of lower limb revascularization, it is difficult to know to what extent these data reflect lifestyle, socio-economic factors, unmet health care need or true ethnic and racial differences in the disease processes or access to services.…”
Section: Secondary Preventionmentioning
confidence: 98%
“…The incidence and prevalence of AAA are increasing in SSA, while decreasing in WW [116]. Aortic aneurysms occur about 15 years earlier in blacks compared to whites in the Southern African region [117,118].…”
Section: Aortic Aneurysmsmentioning
confidence: 99%
“…Hospital-based studies in Zimbabwe and South Africa have shown that hypertension and syphilis are the most frequent risk factors in black Africans, while hypertension and IHD are the most prevalent risk factors in Caucasians [117], and half of aneurysms in black Africans are of non-atherosclerotic origin (mainly due aorto-arteritis) [118]. In high-income countries, risk factors of TAA which is largely a degenerative disease include age, male gender, all atherosclerotic risk factors, aortitis, connective tissue disorders like Marfan, Loeys-Dietz, or Ehlers-Danlos syndromes, bicuspid aortic valve, and Turner syndrome.…”
Section: Aortic Aneurysmsmentioning
confidence: 99%
“…17,18 With the patient in the supine position, the abdominal aorta is scanned at the level of the iliac artery bifurcation with a convex or cardiac transducer (both low-frequency), since approximately 90% of AAAs occur inferiorly to the renal arteries. 19,20 For the identification of the aorta, the vertebral bodies, which are hyperechoic and generate the artifact acoustic shadow, are the anatomical landmark. The aorta is identified to the left of the midline, anterior to the vertebral bodies, whereas the inferior vena cava is seen to the right side.…”
Section: Case Reportmentioning
confidence: 99%